Multiple crack propagation by DBEM in a riveted butt-joint: a simplified bidimensional approach (Fracture and Structural Integrity, 2016)
A Multi-Site Damage (MSD) crack growth simulation is presented, carried out by means of Dual Boundary Element Method (DBEM), in a two-dimensional analysis of a cracked butt-joint made of aluminium 2024 T3. An equivalent crack length is proposed for an approximated 2D analysis of a 3D problem where the crack front assumes a part elliptical shape due to secondary bending effects. The assumptions made to perform such simplified bidimensional analyses are validated by comparing numerical results with experimental data, the latter obtained from a fatigue tested riveted butt-joint.
Keywords: DBEM; LEFM